Os novos desafios da fidelidade partidária a partir do elo entre os partidos e as ideologias políticas - Portela, Thiago Barreto (2016)
Discussion about political reform is the common schedule in all societies, behold, it is impossible to please all the interests involved in Brazilian political system operation, although there is one topic that always meets the consensus in this context: the need for a coherent political representation with the will of the people. It seems unanimous that the democratic system is unhappy with their representatives, mainly by the recent demonstrations in which the main insurgency takes place against the lack of coherence between the actions of agents and the interests of the population, in times when the will of the sovereign power appears to achieve personal motives of representatives, forgetting the public interest that exists in the real holders of that power. Accordingly, given that the Brazilian representative democracy goes, first of all, by the intermediation of political parties before the seal to single application, this work is scoped to identify and propose solutions to the crisis of representation of holders of elective offices and political parties which are linked. To achieve this goal, it was decided to develop a descriptive exploratory study of a qualitative nature, made possible by a literature research on doctrinal legislative and jurisprudential production from authors that focus on the theme chosen as the object of this study, and an analysis of the ideological regiment described in party statutes. Then, investigates the contours of party loyalty to develop it beyond its usefulness against the party migration, emphasizing the concept that ensures fairness between political representative and political party ideology established in its statutes, since that only in this way, party loyalty will function as a real instrument promoter of democracy.